Development and Application of Well-Test Model after Injection Biological Nanomaterials. (11th April 2022) - Feng, Qing; Gao, Ping; Chen, Xianchao; Li, Jiang; Zhou, Jingchao; Qian, Feng; Li, Shengsheng; Sun, Yanni; Wang, Yingying
Abstract : Nanomaterials are gradually shining in the petroleum industry and have made great achievements in EOR, pipeline coating, fracturing, and other aspects. In practical application, they have the advantages of long validity period and more environmental friendliness. At the same time, due to the short effective period of conventional plugging removal measures such as acidizing and fracturing, which are not friendly to the environment, nanomaterials are gradually applied to reduce pressure and increase injection of injection wells, and good application results are obtained. In this study, a new biological nanomaterial with long-term injection enhancement characteristics was evaluated. To have a better understanding of the reservoir performance of water injection wells after pressure reduction and injection increase measures, it is necessary to establish the well test model after the step-down and injection increase measures of biological nanomaterials that are taken for water injection wells. In this paper, the influence of the injection amount of bionanomaterials on the permeability is studied, and the rule of the permeability around the injection well with the distance from the bottom of the well is analyzed. On this basis, the flow mathematical model of three zones (inner zone, transition zone, and outer zone) of bionanosolution is established. Then, using the basic principles of fluid mechanics and the Laplace transform principle, a mathematical model of the bottom hole pressure response of water injection wells in the third zone of the bionanosolution reservoir is obtained, and the influence of the key process parameters of the bionanosolution water injection on the bottom hole pressure is analyzed. The established well test interpretation model can be used to calculate the near wellbore permeability, reservoir skin factor, reservoir sweep radius, and reservoir resistance coefficient. Based on application examples, it was determined that the fitting results of the interpretation chart are in good agreement with the field test data, and the reservoir parameters obtained from the interpretation are reasonable and reliable. The findings of this study can help for better understanding of the dynamic change law of reservoir after injection of biological nanomaterials or similar plugging removal measures (the improvement effect varies with the distance from the bottom hole). To the best of our knowledge, it is the first paper on the application of biological nanomaterials in reducing pressure and increasing injection in injection wells.